Thermoperiodic Control of Hypocotyl Elongation Depends on Auxin-Induced Ethylene Signaling That Controls Downstream PHYTOCHROME INTERACTING FACTOR3 Activity. Issue 2 (16th December 2014) - Bours, Ralph; Kohlen, Wouter; Bouwmeester, Harro J.; van der Krol, Alexander
Abstract : Antiphase light and temperature cycles disrupt an auxin-ethylene-induced signaling cascade, leading to reduced hypocotyl elongation. Abstract: We show that antiphase light-temperature cycles (negative day-night temperature difference [−DIF ]) inhibit hypocotyl growth in Arabidopsis ( Arabidopsis thaliana ). This is caused by reduced cell elongation during the cold photoperiod. Cell elongation in the basal part of the hypocotyl under −DIF was restored by both 1-aminocyclopropane-1-carboxylic acid (ACC; ethylene precursor) and auxin, indicating limited auxin and ethylene signaling under −DIF . Both auxin biosynthesis and auxin signaling were reduced during −DIF . In addition, expression of several ACC Synthase was reduced under −DIF but could be restored by auxin application. In contrast, the reduced hypocotyl elongation of ethylene biosynthesis and signaling mutants could not be complemented by auxin, indicating that auxin functions upstream of ethylene. The PHYTOCHROME INTERACTING FACTORS ( PIFs ) PIF3, PIF4, and PIF5 were previously shown to be important regulators of hypocotyl elongation. We now show that, in contrast to pif4 and pif5 mutants, the reduced hypocotyl length in pif3 cannot be rescued by either ACC or auxin. In line with this, treatment with ethylene or auxin inhibitors reduced hypocotyl elongation in PIF4 overexpressor ( PIF4ox ) and PIF5ox but not PIF3ox plants. PIF3 promoter activity was strongly reduced under −DIF but could be restored by auxin application in an ACC Synthase -dependent manner. Combined, these results show that PIF3 regulates hypocotyl length downstream, whereas PIF4 and PIF5 regulate hypocotyl length upstream of an auxin and ethylene cascade. We show that, under −DIF, lower auxin biosynthesis activity limits the signaling in this pathway, resulting in low activity of PIF3 and short hypocotyls.